CHARACTERISTICS OF SWEET POTATO INSTANT CREAM SOUP FOR EMERGENCY FOOD - Marleen Sunyoto; Robi Andoyo; Intan Btari Dwiastuti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2018)
A convenient food such as instant cream soup is the most suitable choice for practical lifestyle but can also be applied in an emergency situation such as in an area affected by disaster. The addition of milk powder as the main ingredient in cream soup creates a complex binding of fat and starch that complicates the rehydration process and affects other physical appearances. This research aimed to obtain the appro-priate concentration of full cream milk powder to obtain the best physical and chemical characteristics and the most preferable instant cream soup of dried sweet potato. Research method used was a randomized block design with six variables and two repetitions. Instant cream soup with 20% full cream milk powder gave the best physical and chemical characteristic and organoleptically preferred by panelists. The physi-cal and chemical characteristic of the most preferred soup had 6% water content, 95.47% rehydration po-wer, 18% protein, 20.7% fat, 1080 cP viscosity, 30.5% yield. The most favored by panelists were flavor, aroma, colour and thickness after rehydrated.